2018
DOI: 10.1002/ajim.22877
|View full text |Cite
|
Sign up to set email alerts
|

Are there health benefits of being unionized in late career? A longitudinal approach using HRS

Abstract: The reasons for the associations found in this paper need to be explored in further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A third type of studies has very recently focused on the individual relationship between union membership – and, to a lesser extent, presence – and health mainly using individual longitudinal data in the US and the UK. These studies have demonstrated contradictory results that show either a positive 38,39 or a negative relationship 3 mainly due to the nature of the variables used to capture trade union presence or membership and the control variables included in the models. A few other studies have focused on the benefits of using a longitudinal approach to assess the association between union membership and wages 40 or job satisfaction 41 but such a perspective is still rare when looking at health, and particularly mental health.…”
Section: Discussionmentioning
confidence: 99%
“…A third type of studies has very recently focused on the individual relationship between union membership – and, to a lesser extent, presence – and health mainly using individual longitudinal data in the US and the UK. These studies have demonstrated contradictory results that show either a positive 38,39 or a negative relationship 3 mainly due to the nature of the variables used to capture trade union presence or membership and the control variables included in the models. A few other studies have focused on the benefits of using a longitudinal approach to assess the association between union membership and wages 40 or job satisfaction 41 but such a perspective is still rare when looking at health, and particularly mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, collective bargaining and trade union membership may also play a role in explaining older workers' health variations. Using the Health and Retirement Study for the United States, I have shown that unionized workers are less likely than non-unionized workers to experience a negative change in self-perceived health and depression level during the different types of late career transitions (Wels 2018b). Unionized workers are also more likely to retire before non-unionized workers.…”
Section: The Association Between Late Career Transitions and Healthmentioning
confidence: 99%
“…The association captured in this paper corresponds to what was observed during a particular period, particularly characterised both by restricted access to this arrangement and by a less positive impact on the calculation of the state pension.It is based on a two-wave sequence and does not capture the long-run changes in SPH, depression level and quality of life. Even though extending the analysis to three waves would not be likely to affect the sense of the association significantly (Wels, 2018), it can be expected that the long-run impact of change in working time might differ from the short-term impact (Coe and Zamarro, 2011). Although, this would reduce the size of the sample drastically, particularly because of a relatively high attrition rate.It controls for the sector of activity but does not look in depth at what the dynamics are that might be observed at the sector level, particularly in sectors of activity characterised by shift work, night work or short-term contracts.It uses different models for distinguishing those who reduced working time in addition to social benefits from those who did not.…”
Section: Limitationsmentioning
confidence: 99%
“…It is based on a two-wave sequence and does not capture the long-run changes in SPH, depression level and quality of life. Even though extending the analysis to three waves would not be likely to affect the sense of the association significantly (Wels, 2018), it can be expected that the long-run impact of change in working time might differ from the short-term impact (Coe and Zamarro, 2011). Although, this would reduce the size of the sample drastically, particularly because of a relatively high attrition rate.…”
Section: Limitationsmentioning
confidence: 99%